Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

Short-chain PFAS perinatal exposure induces cognitive dysfunction and glial activation in adult rats - G. Foiani; M. Moretti; C. Zanardello; M. Sannia; E. Melchiotti; A. Vitola; F. Gallocchio; L. Lorenzini; L. Giardino; F. Mutinelli; L. Calzà; M. Vascellari (Journal of Comparative Pathology, 2025)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

How do macroconsumers interact with insect shredders in streams? A laboratory test using shrimp and caddisfly larvae that build cases with different organic materials - Pâmela Barbosa; Walace P. Kiffer; Larissa C. Costa; Flávio Mendes; Marcelo S. Moretti (Limnologica, 2023)

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

Leaf-associated macroinvertebrate assemblage and leaf litter breakdown in headwater streams depend on local riparian vegetation - Rebecca Oester; Paula C. dos Reis Oliveira; Marcelo S. Moretti; Florian Altermatt; Andreas Bruder (Hydrobiologia, 2023)
Headwater streams harbor diverse macroinvertebrate communities and are hotspots for leaf litter breakdown. The process of leaf litter breakdown mediated by macroinvertebrates forms an important link between terrestrial and aquatic ecosystems. Yet, how the vegetation type in the local riparian zone influences leaf-associated macroinvertebrate assemblages and leaf litter breakdown rates is still not resolved. We investigated how leaf-associated macroinvertebrate assemblages and leaf litter fragmentation rates differ between forested and non-forested sites using experimental leaf litter bags in sixteen sites paired across eight headwater streams in Switzerland. Our results show that sensitive taxa of the invertebrate orders Ephemeroptera, Plecoptera and Trichoptera (EPT) and the functional group of shredders were strongly associated with forested sites with overall higher values of abundance, diversity, and biomass of EPTs in forested compared to non-forested sites. However, the importance of riparian vegetation differed between study regions, especially for shredders. Fragmentation rates, which are primarily the result of macroinvertebrate shredding, were on average three times higher in forested compared to non-forested sites. Our results demonstrate that not only the composition of the aquatic fauna but also the functioning of an essential ecosystem process depend on the vegetation type in the local riparian zone.

Diverse magma storage and major and volatile magma composition: What are the implications on the eruptive style across a volcanic arc? An example of the Lesser Antilles Arc - A. Metcalfe; S. Moune; J.-C. Komorowski; R. Robertson; T.E. Christopher; E.P. Joseph; R. Moretti (Earth-Science Reviews, 2023)

Feline injection-site sarcomas (FISSs): could the assessment of tumour-infiltrating lymphocytes (TILs) help in prog-nostic evaluations? - I. Porcellato; E. Treggiari; V. Gismondi; I. Di Matteo; C. De Feo; G. Moretti; P. Roccabianca; E. Lepri; M. Sforna; C. Brachelente (Journal of Comparative Pathology, 2023)

Sex-dependent modulation of caerulein-induced acute pancreatitis in C57BL/6J mice: histopathological and immunohistochemical characterization - L. Bertola; G. Pepe; A. Dolce; A. Cappelleri; S. Canesi; P. Moretti; A. Giordano; E. Scanziani; E. Vegeto; C. Recordati (Journal of Comparative Pathology, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Morpho-sedimentary dynamics of Torre Guaceto beach (Southern Adriatic Sea, Italy) - I Lapietra; S Lisco; G Mastronuzzi; S Milli; C Pierri; F Sabatier; G Scardino; M Moretti (Journal of Earth System Science, 2022)

Early nitrogen supply as an alternative management for a cover crop-maize sequence under a no-till system - Letusa Momesso; Carlos A. C. Crusciol; Rogério P. Soratto; Carlos A. C. Nascimento; Ciro A. Rosolem; Luiz G. Moretti; Eiko E. Kuramae; Heitor Cantarella (Nutrient Cycling in Agroecosystems, 2021)
Optimizing agronomic efficiency (AE) of nitrogen (N) fertilizer use by crops and enhancing crop yields are challenges for tropical no-tillage systems since maintaining crop residues on the soil surface alters the nutrient supply to the system. Cover crops receiving N fertilizer can provide superior biomass, N cycling to the soil and plant residue mineralization. The aims of this study were to (i) investigate N application on forage cover crops or cover crop residues as a substitute for N sidedressing (conventional method) for maize and (ii) investigate the supply of mineral N in the soil and the rates of biomass decomposition and N release. The treatments comprised two species, i.e., palisade grass [ Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster] and ruzigrass [ Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins], and four N applications: (i) control (no N application), (ii) on live cover crops 35 days before maize seeding (35 DBS), (iii) on cover crop residues 1 DBS, and (iv) conventional method (N sidedressing of maize). The maximum rates of biomass decomposition and N release were in palisade grass. The biomass of palisade grass and ruzigrass were 81 and 47% higher in N application at 35 DBS compared with control in ruzigrass (7 Mg ha −1 ), and N release followed the pattern observed of biomass in palisade and ruzigrass receiving N 35 DBS (249 and 189 kg N ha −1 ). Mineral N in the soil increased with N application regardless of cover crop species. Maize grain yields and AE were not affected when N was applied on palisade grass 35 DBS or 1 DBS (average 13 Mg ha −1 and 54 kg N kg −1 maize grain yield) compared to conventional method. However, N applied on ruzigrass 35 DBS decreased maize grain yields. Overall, N fertilizer can be applied on palisade grass 35 DBS or its residues 1 DBS as a substitute for conventional sidedressing application for maize.

Use of radiofrequency electromagnetic radiation to remove biofilms from canvasses - P. Cennamo; N. Pasquino; C. Ciniglia; A. Moretti; P. Caputo (Aerobiologia, 2020)

Protective effect of nutraceutical food on the intestinal mucosa of juvenile pacu Piaractus mesopotamicus under high stocking density - Mariana C. F. Pontin; Wiolene M. Nordi; Jéssica Pampolini; Raul Machado-Neto; Débora B. Moretti (Aquaculture International, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The longer the conditioning, the better the quality? The effects of leaf conditioning time on aquatic hyphomycetes and performance of shredders in a tropical stream - Cinthia G. Casotti; Walace P. Kiffer; Larissa C. Costa; Pâmela Barbosa; Marcelo S. Moretti (Aquatic Ecology, 2019)

Infection incidence, kernel colonisation, and mycotoxin accumulation in durum wheat inoculated with Fusarium sporotrichioides, F. langsethiae or F. poae at different growth stages - L. Nazari; E. Pattori; S. Somma; V. Manstretta; C. Waalwijk; A. Moretti; G. Meca; V. Rossi (European Journal of Plant Pathology, 2019)

Claviceps arundinis identification and its role in the die-back syndrome of Phragmites australis populations in central Italy - M. Cerri; L. Reale; C. Moretti; R. Buonaurio; A. Coppi; V. Ferri; B. Foggi; D. Gigante; L. Lastrucci; M. Quaglia; R. Venanzoni; F. Ferranti (Plant Biosystems, 2018)

Monitoring of ochratoxin A and ochratoxin-producing fungi in traditional salami manufactured in Northern Italy - C. Merla; G. Andreoli; C. Garino; N. Vicari; G. Tosi; M. L. Guglielminetti; A. Moretti; A. Biancardi; M. Arlorio; M. Fabbi (Mycotoxin Research, 2018)

Advanced interpretation of interferometric SAR data to detect, monitor and model ground subsidence: outcomes from the ESA-GMES Terrafirma project - F. Raspini; S. Bianchini; S. Moretti; C. Loupasakis; D. Rozos; J. Duro; M. Garcia (Natural Hazards, 2016)

Diversity of phototrophic components in biofilms from Piperno historical stoneworks - P. Cennamo; P. Caputo; C. Marzano; A. Z. Miller; C. Saiz-Jimenez; A. Moretti (Plant Biosystems, 2016)

Passive acoustic density estimation of sperm whales in the Tongue of the Ocean, Bahamas - Jessica A. W ard; Len Thomas; Susan Jarvis; Nancy DiMarzio; David Moretti; Tiago A. Marques; Charlotte Dunn; Diane C laridge; Eva Hartvig; Peter Tyack (Marine Mammal Science, 2012)
Long‐term passive acoustic monitoring of marine mammals on navy ranges provides the opportunity to better understand the potential impact of sonar on populations. The navy range in Tongue of the Ocean (TOTO), Bahamas contains extensive hydrophone arrays, potentially allowing estimation of the density of deep diving, vocally active species such as the sperm whale ( Physeter macrocephalus ). Previous visual surveys in TOTO have been of limited spatio–temporal coverage and resulted in only sporadic sightings of sperm whales, whereas passive acoustic observations suggest the species is present year round. However, until now the means of acoustically determining the specific number of individuals in each cluster has been limited. We used recently developed algorithms to identify the number of echolocating whales present during a 42 d study period. We screened a 297 h acoustic data set to determine the proportion of time animals were present; fifty 10 min samples during presence were analyzed to estimate the number of individuals vocalizing during each sample. These counts were combined with an independent estimate of the proportion of 10 min periods when tagged animals vocalize. The estimated average density was 0.16 whales/1,000 km 2 (CV 27%; 95% CI 0.095–0.264). The method is potentially applicable to other areas containing dense hydrophone arrays.

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Anti-HIV Drugs Nevirapine and Efavirenz Affect Anxiety-Related Behavior and Cognitive Performance in Mice - Pedro R. T. Romão; Joelson C. Lemos; Jeverson Moreira; Gisele de Chaves; Morgana Moretti; Adalberto A. Castro; Vanessa M. Andrade; Carina R. Boeck; João Quevedo; Elaine C. Gavioli (Neurotoxicity Research, 2011)

Trichothecene and beauvericin mycotoxin production and genetic variability in Fusarium poae isolated from wheat kernels from northern Italy - S. Somma; C. Alvarez; V. Ricci; L. Ferracane; A. Ritieni; A. Logrieco; A. Moretti (Food Additives & Contaminants: Part A, 2010)

Blockade of adenosine A2A receptor counteracts neuropeptide-S-induced hyperlocomotion in mice - Carina R. Boeck; Caroline Martinello; Adalberto A. de Castro; Morgana Moretti; Tiago dos Santos Casagrande; Remo Guerrini; Girolamo Calo’; Elaine C. Gavioli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Determinants for the conservation of a vulnerable fire-dependent species at its marginal range - M. Moretti; C. Staehli; F. Gillet (Plant Ecology, 2008)

Quantifying functional diversity with graph-theoretical measures: advantages and pitfalls - C. Ricotta; M. Moretti (Community Ecology, 2008)

Evaluation of Fusarium solani Hyphae and Conidia Susceptibility to Amphotericin B and Itraconazole: Study of a Clinical Case - A. B. A. Teixeira; M. L. Moretti; P. Trabasso; A. von Nowakonski; F. H. Aoki; A. C. Vigorito; M. Miyaji; K. Nishimura; H. Taguchi; A. Z. Schreiber (Mycopathologia, 2005)

Mainshocks and aftershocks of the 2002 molise seismic sequence, southern Italy - C. Chiarabba; P. De Gori; L. Chiaraluce; P. Bordoni; M. Cattaneo; M. De Martin; A. Frepoli; A. Michelini; A. Monachesi; M. Moretti; G. P. Augliera; E. D'Alema; et al. (Journal of Seismology, 2005)

Potential role of SEN virus on liver enzyme abnormalities in patients positive for hepatitis C virus with or without HIV infection - E. Quiros-Roldan; F. Moretti; C. Torti; V. Tirelli; R. Stellini; S. Pirovano; G. Carosi; L. Imberti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Comparative analysis of early embryonic sunflower cDNA libraries - Ccile Ben; Tarek Hewezi; Marie Franoise Jardinaud; Frdrique Bena; Nathalie Ladouce; Sbastien Moretti; Cecilia Tamborindeguy; Thierry Liboz; Michel Petitprez; Laurent Gentzbittel (Plant Molecular Biology, 2005)

Recessive resistance genes against potyviruses are localized in colinear genomic regions of the tomato (Lycopersicon spp.) and pepper (Capsicum spp.) genomes - G. Parrella; S. Ruffel; A. Moretti; C. Morel; A. Palloix; C. Caranta (Theoretical and Applied Genetics, 2002)

Effect of Fusarium, Paecilomyces and Trichoderma formulations against aphid Schizaphis graminum - S. Ganassi; A. Moretti; C. Stornelli; B. Fratello; A.M. Bonvicini Pagliai; A. Logrieco; M.A. Sabatini (Mycopathologia, 2001)

Molecular tagging of the Am gene from Lycopersicon hirsutum f. glabratum PI 134417 using AFLP markers - G. Parrella; I. Hochu; K. Gebre-Selassié; P. Gognalons; A. Moretti; G. Marchoux; C. Caranta (Acta Physiologiae Plantarum, 2000)

Molecular and Biochemical Characterization of Two Atypical Toxigenic Populations of Fusarium Camptoceras - G. Mule’; C. Altomare; A. Moretti; G. Perrone; A. Logrieco (Cereal Research Communications, 1997)

Clustering of Toxigenic Fungi Determined by rDNA Sequences - G. Mulè; A. Moretti; C. Altomare; A. Logrieco (Cereal Research Communications, 1997)